2013
DOI: 10.1007/s10900-013-9793-7
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being and Perceived Quality of Life in Elderly People Displaced After the Earthquake in L’Aquila, Italy

Abstract: On 6 April 2009, the city of L’Aquila was hit by a violent earthquake that destroyed almost all of its medieval centre, and the surviving inhabitants were evacuated and relocated in temporary quarters or undamaged homes. The aim of this study was to investigate the perceived quality of life of the elderly population 3 years after the earthquake in relation to the social and logistic issues of new housing. The study was carried out between October 2011 and March 2012, and involved 571 subjects aged over 65 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
(59 reference statements)
1
20
0
Order By: Relevance
“…life than others, 8 and that those who have relocated to temporary trailer or newly purchased/rented residence are more likely to experience post-traumatic stress disorder symptoms and psychological distress. [9][10][11] Possible reasons for this housing-related effect on health include differences in both living environment and social support from relatives and friends.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…life than others, 8 and that those who have relocated to temporary trailer or newly purchased/rented residence are more likely to experience post-traumatic stress disorder symptoms and psychological distress. [9][10][11] Possible reasons for this housing-related effect on health include differences in both living environment and social support from relatives and friends.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Findings showed that younger women felt powerless but not depressed and were well motivated to deal with their own clinical treatment protocols with good compliance, and they obtained fast, positive outcomes. Lately, some authors have extended such findings to the posttraumatic growth model of Tedeschi and Calhoun (2004): the posttraumatic growth is a construct whereby positive behavioral changes can be identified in dealing with and negotiating traumatic experiences (Giuliani et al, 2014). Moreover, Kolokotroni et al (2014) analyzed the impact of psychosocial factors on posttraumatic growth after BC diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that the prevalence of depression in survivors aged 65 years or older was significantly higher than that of young people 3 years after the Chi‐Chi earthquake in Taiwan (Wu et al, ). Moreover, Giuliani et al () noted that older people living in the new town had a poorer perception of their quality of life than their younger counterparts 3 years after the earthquake in L'Aquila in Italy.…”
Section: Introductionmentioning
confidence: 99%